Konstruksi Identitas Virtual Muslimah Preneur: Mediatisasi dan Komodifikasi Agama dalam Akun Instagram @auliyafadlilah - Alamsyah, Femi Fauziah; Hakim, Hari Rahman; Latifah, Siti Lutfi; Hamidah, Hasya Dinan (STAI Bumi Silampari, 2024)
In the last decade, the number of Muslimah-preneurs active on social media has significantly increased, especially on Instagram. Muslimah-preneurs, or Muslim women entrepreneurs, utilize Instagram to promote their businesses and build an identity as entrepreneurs committed to integrity and Islamic values. The Instagram account @auliyafadlilah serves as an intriguing example of how a Muslimah-preneur constructs a complex virtual identity. This study focuses on the identity construction of Auliya Fadlilah as a Muslimah-preneur on Instagram, the mediatization of religion in her content, and the commodification of religion for marketing purposes. The study aims to explore the virtual identity construction process and identify commodification practices resulting from the mediatization of religion on Instagram. A qualitative method was employed, using Michel Foucault's technologies of the self framework, which explains how individuals transform themselves to achieve their desired perfection. The findings reveal that the construction of a Muslimah-preneur's virtual identity, the mediatization of religion, and the commodification of religion are interrelated and mutually reinforcing on social media. Auliya Fadlilah utilizes Instagram to shape her identity as a successful and religious Muslimah-preneur. Through posts and captions that highlight Islamic values, personal stories, and business achievements, Auliya constructs an inspiring and trustworthy self-image for her followers. The use of religious language and symbols strengthens this identity and fosters emotional connections with her audience. Mediatization of religion occurs as Auliya employs Instagram to disseminate Islamic teachings and values, making them more accessible to a wider audience. The commodification of religion emerges as a consequence of this mediatization, where religious elements such as halal products and endorsements aligned with Islamic values are commercialized to generate financial profit. The simultaneous interplay of virtual identity construction, mediatization, and commodification of religion creates a demand for products and services aligned with Islamic values.